Numerical Study of Piled Raft Foundation in Non-Homogeneous Soil Using Finite Element Method (Journal of Engineering, 2023)
This paper analyzes a piled-raft foundation on non-homogeneous soils with variable layer depth percentages. The present work aims to perform a three-dimensional finite element analysis of a piled-raft foundation subjected to vertical load using the PLAXIS 3D software. Parametric analysis was carried out to determine the effect of soil type and initial layer thickness. The parametric study showed that increasing the relative density from 30 % to 80 % of the upper sand layer and the thickness of the first layer has led to an increase in the ultimate load and a decrease in the settlement of piled raft foundations for the cases of sand over weak soil.  In clay over weak soil, the ultimate load of the piled raft foundation was increased, and the settlement decreased by increasing the clay cohesion of the upper layer from 20 kPa to 70 kPa. It was observed that the load shared by the raft was very effective when using dense sand in the upper layer. In the case of dense sand over stiff clay, the percent of load carried by the raft is (30-40) %. Although, for the case of stiff clay over soft clay, the load percentage was almost constant (16-20) %. While for other issues, the sharing load of raft foundation was close and had the same behavior, the load carried by raft is between (8-12) %.